2008
DOI: 10.1039/b803364a
|View full text |Cite
|
Sign up to set email alerts
|

s-Block metal complexes of a bulky, donor-functionalized allyl ligand

Abstract: Crystallographic and NMR spectroscopic studies on allyl complexes of lithium, potassium and magnesium containing an O-donor functionality are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…[40] The asymmetric allyl coordination in 8 is likely to arise from steric clashes between the three pmdeta ligands, and may indicate partial delocalization of the formal negative charges within the allyl anions as has previously been observed in intramolecularly solvated alkalimetal allyl compounds. [24][25][26][27]30,41] Indeed, it is notable that the allylic carbon-carbon bonds in 8 are unequal in length, with C(2)-C(3) and C(3)-C(4) being 1.382(7) and 1.426(7) Å, C(17)-C(18) and C(18)-C(19) being 1.367(7) and 1.424 (7), and C(32)-C(33) and C(33)-C(34) being 1.379 (7) 3 form, revealing that these two configurations are very close in energy. Consequently, it is possible that environment effects may play a role in determining the preference of one stereochemistry over the other.…”
Section: Resultsmentioning
confidence: 99%
“…[40] The asymmetric allyl coordination in 8 is likely to arise from steric clashes between the three pmdeta ligands, and may indicate partial delocalization of the formal negative charges within the allyl anions as has previously been observed in intramolecularly solvated alkalimetal allyl compounds. [24][25][26][27]30,41] Indeed, it is notable that the allylic carbon-carbon bonds in 8 are unequal in length, with C(2)-C(3) and C(3)-C(4) being 1.382(7) and 1.426(7) Å, C(17)-C(18) and C(18)-C(19) being 1.367(7) and 1.424 (7), and C(32)-C(33) and C(33)-C(34) being 1.379 (7) 3 form, revealing that these two configurations are very close in energy. Consequently, it is possible that environment effects may play a role in determining the preference of one stereochemistry over the other.…”
Section: Resultsmentioning
confidence: 99%
“…[19] Support for this conclusion is found in a related lithium complex formed from the tetrahydrofurfuryl-substituted derivative of the AЈ ligand ( Figure 2). [33] The dimeric complex has Li1-O1 and Li2-O2 bond lengths that are indistinguishable at 1.87 Å, and the C-C allyl bonds are slightly more delocalized (∆ = 0.052 Å) than in {Li [1,1Ј,3- Figure 3). [42] The π-bonded allyl ligands are at an angle of 60-62°from the major chain axes, and the Li-C distances range from 2.16 Å to 2.35 Å.…”
Section: Peculiarities Of Halide Metathesis Synthesismentioning
confidence: 98%
“…The reaction of Li[AЈ] with tetrahydrofurfuryl tosylate produces [4-(tetrahydrofuran-2-yl)but-1-ene-1,3-diyl]bis(trimethylsilane) (Scheme 6); it can subsequently be deprotonated with alkyllithium reagents or MgBu 2 to produce new metal complexes. [33] Scheme 6. Synthesis of a thf-functionalized allyl ligand.…”
Section: General Preparative Routesmentioning
confidence: 99%
See 1 more Smart Citation
“…Density functional theory (DFT) calculations suggested that a base-free Be(C3H3E2)2 (E = H, SiH3) complex would be more slightly more stable with delocalized, π-type allyls than with monodentate, sigmabonded ligands (Scheme 1). If so, beryllium allyls would join those of magnesium, in which monodentate allyl ligands are uniformly found in complexes that are ether-solvated [12], but that in the absence of ethers, cation-π interactions with the metal can create "slipped-π" bonding [13]. Scheme 1.…”
Section: Solid-state Synthesismentioning
confidence: 99%